PENGEMBANGAN KAPASITAS INTELEKTUAL, SPIRITUAL, DAN MORAL, PEMBELAJARAN SEPANJANG HAYAT, PENINGKATAN KUALITAS DAN ORGANISASI, HADIST NABI TENTANG MENUNTUT ILMU DAN PERBAIKAN DIRI - Rahmah; Ibnul Amin; Suraijiah; Fahmi Riady; Rusdiana (Jurnal Riset Multidisiplin Edukasi, 2026)
Islamic education essentially does not only focus on mastering knowledge, but also emphasizes the formation of human spirituality and morality. Rapid developments in modern times require individuals to continuously learn and develop themselves in order to face various life challenges. Therefore, the development of intellectual, spiritual, and moral capacities becomes an important necessity in personal and organizational life. This study aims to analyze the concept of intellectual, spiritual, and moral development from an Islamic perspective, understand the concept of lifelong learning, and examine the Prophet’s traditions regarding seeking knowledge and self-improvement. This research uses a library research method with a qualitative descriptive approach. Data sources were obtained from books, scientific journals, articles, and hadith related to self-development and Islamic education. The results show that Islam strongly emphasizes the balance between intellectual intelligence, spiritual strength, and moral quality in shaping superior human beings. Intellectual development is carried out through learning processes, critical thinking, and mastery of knowledge. Spiritual development is realized through worship, remembrance of Allah, and strengthening one’s relationship with Allah SWT, while moral development is manifested through the formation of noble character in daily life. The concept of lifelong learning in Islam indicates that learning is a continuous process throughout life and is considered part of worship. The Prophet’s hadiths also motivate Muslims to continuously seek knowledge and improve themselves. In the context of organizations and educational institutions, the development of intellectual, spiritual, and moral capacities is very important to improve the quality of human resources so they can face modern challenges without losing Islamic values. Thus, the integration of intellectual, spiritual, moral, and lifelong learning becomes an important foundation in shaping qualified individuals who are beneficial to society.